Perencanaan Strategi Pendidikan di MIN 05 Labuhanbatu - Mesiono; Adolina; Raudatun Annisa; Rizza Fikri Al-Faris; Yunisa Indriyani (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the strategic planning of education at MIN 05 Labuhanbatu. This study employs a qualitative approach with a descriptive method, using data collection techniques through interviews, observations, and document studies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The subjects of this research are the head of the madrasa, teachers, and students at MIN 05 Labuhanbatu. The results show that the strategic planning of education at MIN 05 Labuhanbatu includes: (1) analysis of internal and external environments, (2) setting of vision, mission, and goals, (3) strategy selection, (4) strategy implementation, and (5) evaluation and control. It can be concluded that MIN 05 Labuhanbatu has conducted educational strategic planning well, encompassing environmental analysis, vision, mission, and goal setting, strategy selection, implementation, as well as evaluation and control. This indicates that the madrasa has good management in handling education.